Cumplimiento del proceso de baja de bienes de propiedad, planta y equipo en el GAD municipal del cantón Urdaneta, periodo 2021. - Chevez Bastidas, Stephany Janeth (2022)
This case study raises the non-compliance of the processes for the disposal of institutional assets, as required by the corresponding public sector regulations applicable to the Property, Plant and Equipment item, despite having the list of assets in bad condition , dentified in the physical verification, the entity has not carried out the respective administrative management, which prevents considering the effective reconciliation of accounting balances in the financial statements, Thus, once the processes are executed this reflects reasonable results in the financial information of the Municipal Decentralized Autonomous Government of Canton Urdaneta in the period, it is concluded advising the administrative area, that any asset identified in bad condition or not useful for the entity is included in the list of assets for the cancellation, which according to its nature can be donation or free transfer, scrapping, destruction or sale, also consider the respective accounting adjustments at the end of the administrative act of cancellation all this considering the regulations, respective regulations of the public sector being these; Regulations for the Administration and Control of Public Sector Assets, Internal Control Standards of the Comptroller General of the State, it should be noted that a private entity is managed with the International Accounting Standards No. 16, (there are systems within the public sector entities designated with private sector standards).